2022
DOI: 10.1002/prop.202200009
|View full text |Cite
|
Sign up to set email alerts
|

Quintessence and the Swampland: The Parametrically Controlled Regime of Moduli Space

Abstract: We provide evidence that slow roll is not possible in any parametrically controlled regime of the moduli space of string theory. This is proven in full generality in the asymptotic limit of the moduli space of type II and heterotic Calabi-Yau compactifications for the dilaton and any number of Kähler moduli. Our results suggest that in order to build quintessence into string theory one must work in the interior of moduli space where numerical, even if not parametric, control could still be achieved.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 39 publications
(55 reference statements)
2
29
0
Order By: Relevance
“…Not only do these solutions exhibit scale separation, they do so with parametric control, meaning that the separation can be tuned thanks to a parameter. It is important to distinguish the two concepts, as stressed in [23] for de Sitter solutions (see also [54]): one can simply look for a satisfactory hierarchy of scales in a given solution, without asking for this hierarchy to be tunable. Another concept is that of classicality of a 10d supergravity solution, namely whether it belongs to the classical regime of string theory.…”
Section: Scale Separationmentioning
confidence: 99%
“…Not only do these solutions exhibit scale separation, they do so with parametric control, meaning that the separation can be tuned thanks to a parameter. It is important to distinguish the two concepts, as stressed in [23] for de Sitter solutions (see also [54]): one can simply look for a satisfactory hierarchy of scales in a given solution, without asking for this hierarchy to be tunable. Another concept is that of classicality of a 10d supergravity solution, namely whether it belongs to the classical regime of string theory.…”
Section: Scale Separationmentioning
confidence: 99%
“…Furthermore, for the Standard Model anti-brane the amount of warping provided by the fluxes can also be used in order to get the appropriate scales. See [115,116,117] for a recent critical assessment of realising quintessence within string compactifications.…”
Section: Uv Embeddingsmentioning
confidence: 99%
“…For this mechanism to work for a single (real) field, in general the corresponding potential must have a very flat profile along the physical trajectory. However [14] showed that slow roll quintessence cannot be achieved in any parametrically controlled regime of the moduli space of string theory. Viable quintessence models could therefore exist only in the bulk of moduli space where numerical, even if not parametric, control could still be achieved.…”
Section: Introductionmentioning
confidence: 99%